Avaliação do potencial antioxidante de coprodutos de indústrias de suco de uva e de vinho visando sua aplicação em linguiça de frango - Casagrande, Maira (2014)
The search for natural products and the risk to human health due to consumption of synthetic antioxidants encourage research for the discovery of new potential sources of bioactive compounds. The production of wine and grape juice generates large amounts of pomace rich in phenolic compounds that can be used as natural antioxidants. The objective of this work was to evaluate the extraction of bioactive compounds from pomace of grape juice (BUS) and wine (BUV) industry using a 24-1 fractional factorial design. After the determination of the better extraction condition for both co-products, was determinate with the total antioxidant activity using different determination methodology, and among the two samples (BUS and BUV), which obtained the largest quantifications by these methodologies, would be tested in the processing of chicken sausage in order to verify the inhibition of formation of malondialdehyde compared to synthetic antioxidant ES (sodium erythorbate)The independent variables studied were grape fruit pomace (GJP) and grape wine pomace (GWP), both temperature (40 and 60°C), extraction time of compounds (15- 45 min), and solvent type (acetone and ethanol, 80%). Co-products extracts were analyzed in terms of the contents of TPC by Folin Ciocalteu and scavenging activity of the DPPH• radical. After determining the best extraction method of bioactive compounds in each pomace (GJP and GWP), we determined the amount of antioxidants required to decrease the initial concentration of DPPH at 50% (IC50), ABTS• radical scavenging activity, Ferric Reducing Antioxidant Power (FRAP), and inhibition percentage by autoxidation of the system of β-carotene/linoleic acid. The DPPH radical scavenging activity in the 16 tests ranged from 65-149 μmol Trolox.g-1, and the TPC from 18-35 mg GAE.g-1 (gallic acid equivalent). The statistical analysis explains the significance of the effects and coefficients of the model generated in terms of their antioxidant activities. The linear regression analysis showed that the model generated explain more than 93% of the data variability. Thus, for both pomaces, acetone 80% was the best solvent for the extraction of antioxidant compounds and the ideal extraction temperature was 60°C. However, the best extraction time for GJP was 15 min and for GWP, 45 min. Under these extraction conditions, GJP showed activity in the DPPH method (EC50), ABTS•+, FRAP, and inhibition percentage at 339 μg.mL-1, 334 μmol TEAC.g-1, 151 μmol Fe2+.g-1and 73%, respectively. The values for GWP were 489 μg.mL-1, 249 μmol TEAC.g-1, 111 μmol Fe2+.g-1 and 68%, respectively. The responses of the factorial design showed that GJP had higher contents of phenolic compounds and antioxidant activity than GWP in its better extractions conditions. Was formulated four different chicken meat sausages: control sample (without antioxidant – T1), sample containing synthetic antioxidant 0.01% (T2), sample containing 2mg.g-1 of GJP extract (T3) and a sample containing 4 mg.g-1 of GJP extract (T4), the GJP extract was utilized lyophilized and in your optimized condition according to the factorial design (acetone 80%, 60ºC, 15 minutos), and the extracts were route-evaporated and lyophilized. The physicochemical and microbiological parameters of all formulations resulted in values that are consistent with current laws. Was observed color variations during the storage period of fresh chicken sausages, treatments T3 and T4 had the highest ΔE and the smaller L * values. T1 and T2 treatments had higher values of a *, b * and C *. The pH showed a reduction for the four formulations of sausages, ranging from 6.71 to 5.99, between treatments. To measure lipid oxidation TBARS methodology was used. Samples containing BUS were able to inhibit lipid oxidation. At time 8 days of storage at 4 ° C, compared to the control, T2 could inhibit the formation of malonaldehyde 0.31%, while the treatments with 2 ad 04 mg.g-1 of lyophilized BUS extract (T3 and T4) inhibited 55% and 73% respectively.